2010
DOI: 10.1590/s0037-86822010000400010
|View full text |Cite
|
Sign up to set email alerts
|

Is severe visceral leishmaniasis a systemic inflammatory response syndrome? A case control study

Abstract: Introduction: The objective of the study is to identify the main risk factors for death by New World visceral leishmaniasis and establish a coherent pathogenic substrate of severe disease based on clinical findings. Methods: Seventy-six deceased inpatients and 320 successfully treated inpatients with VL were studied in a case control study. Results: Bacterial infection and bleeding were mutually exclusive events leading to death. Five risk factors were unique for death by bacterial infection (malnutrition, pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
2
3

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(132 citation statements)
references
References 33 publications
7
120
2
3
Order By: Relevance
“…Considering that other opportunistic diseases frequently develop during VL episodes in VL/HIV patients 33 , there was a highly accentuated death rate due to other causes in the VL/HIV group (12.9%) in comparison to the VL group (0.7%). It has been suggested that knowledge regarding the laboratory and clinical profi les of patients and their association with death from VL could assist in clinical management and reduce lethality [39][40][41] . Therefore, since 2011, the Brazilian Health Ministry (Ministério da Saúde do Brasil) has recommended the differential diagnosis of opportunistic infections and the use of serological tests for HIV in patients with VL in VL-endemic regions such as Tocantins.…”
Section: Rev Soc Bras Medmentioning
confidence: 99%
“…Considering that other opportunistic diseases frequently develop during VL episodes in VL/HIV patients 33 , there was a highly accentuated death rate due to other causes in the VL/HIV group (12.9%) in comparison to the VL group (0.7%). It has been suggested that knowledge regarding the laboratory and clinical profi les of patients and their association with death from VL could assist in clinical management and reduce lethality [39][40][41] . Therefore, since 2011, the Brazilian Health Ministry (Ministério da Saúde do Brasil) has recommended the differential diagnosis of opportunistic infections and the use of serological tests for HIV in patients with VL in VL-endemic regions such as Tocantins.…”
Section: Rev Soc Bras Medmentioning
confidence: 99%
“…The occurrence of death from VL is associated with several factors, including young age and the presence of comorbidities such as infections, malnutrition, and AIDS. The following features have been cited as markers of poor prognosis: fever lasting for more than 60 days, bacterial infection, jaundice, dyspnea, hemorrhage, severe anemia, severe neutropenia, and thrombocytopenia [3][4][5][6][7][8][9][10][11] . In addition, diffi culties in early diagnosis and appropriate treatment administration in many endemic areas are other determining factors of lethality; these issues are mainly caused by restricted access to health services 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as other parasitic genes 10,20,37 and host determinants including host genetics 15 , immune status 8 , and nutrition 2 should be investigated 10 . Because of a likely polygenic infl uence on the phenotype of the disease, as suggested by the multiple molecular mechanisms associated with Leishmania survival in vertebrate hosts 38,39 , and the crucial involvement of the host response, additional kala-azar patients and other genes should be observed before a defi nitive conclusion is reached on the role of virulence factors in the pathogenesis of severe kala-azar.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…With these classic manifestations, clinical presentations including bleeding and bacterial infections are present in the most severe forms of the disease and are associated with mortality 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation